2016
DOI: 10.7575/aiac.ijalel.v.5n.6p.99
|View full text |Cite
|
Sign up to set email alerts
|

Linguistic Levels of Translation: A Generic Exploration of Translation Difficulties in Literary Textual Corpus

Abstract: This case study research was based on a generic exploration of the translation problems that graduate students face in literary translation. Literary translation is fundamental to translation programs at higher education due to the upsurge that has occurred in publishing classical and modern literary works from various cultures. However, literary texts have special characteristics that make the process of transferring them from one language into another a daunting task. Translating literary texts is difficult … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
(44 reference statements)
1
2
0
Order By: Relevance
“…Since the Frayer Model Plus was based on the functionalist approach, the findings of this research were aligned with those of Károly(2014) who concluded that the use of a functional framework developed students' translation as they were able to manage the relationship between text and context based on their cultural and textual awareness. Since students in this research used different online tools, the current results coincided with those of Mahmoud and NourEldin (2021) equivalents, the findings of this research were like those of Madkour (2016) who proved the positive effect of cognitive-based teaching methods on students' performance in translation.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Since the Frayer Model Plus was based on the functionalist approach, the findings of this research were aligned with those of Károly(2014) who concluded that the use of a functional framework developed students' translation as they were able to manage the relationship between text and context based on their cultural and textual awareness. Since students in this research used different online tools, the current results coincided with those of Mahmoud and NourEldin (2021) equivalents, the findings of this research were like those of Madkour (2016) who proved the positive effect of cognitive-based teaching methods on students' performance in translation.…”
Section: Discussionsupporting
confidence: 87%
“…The different cognitive processes required to fill the Frayer Model Plus develop students' understanding of the new concepts (Hunt et al, 2013). Madkour (2016) examined the effect of cognitive-based teaching methods on university students' performance in translation. Quantitative and qualitative data were collected from a focus group of participants.…”
Section: Review Of Literature and Related Studiesmentioning
confidence: 99%
“…Although different sound devices contribute to the overall meaning of a literary work, many students find it difficult to identify these poetic devices. A study by Madkour (2016) supports this finding that the students faced problems transferring sound devices as rhyme, rhythm, alliteration, assonance, and consonance. In relation to this matter, Chan (2020) argues that unlike paradox and oxymoron, which are semantic devices, alliteration and assonance are sonic devices, and this makes it considerably harder to analyze in terms of their contribution to the themes and meaning of a given text.…”
Section: Findings and Discussionmentioning
confidence: 75%
“…The second study was conducted by Okere et al (2018) The goal of this paper was to figure out the reasons behind the linguistic difficulties when translating poetry from the source text in English to the target text in Kiswahili. The third study was conducted by Madkour (2016) This case study thesis was focused on a generic exploration of the translation issues encountered in literary translation by graduate students. The fourth study was conducted by Guerra (2012) to discover the key methods and techniques for translation to address challenges in the translation of cultures.…”
mentioning
confidence: 99%